Porous Silica Coated Ceria as a Switch in Tandem Oxidative Dehydrogenation and Dry Reforming of Ethane with CO2. Issue 15 (10th June 2021) - Li, Yingchun; Li, Linyi; Sun, Wenjing; Chen, Congmei; Luo, Shizhong; Shen, Jun; Jiang, Chengfa; Jing, Fangli
Abstract: The oxidative dehydrogenation of ethane using CO2 as soft oxidant for the production of ethylene, possesses the features of valorization of light alkane and utilization of greenhouse gas. Although a significant challenge, the control of the reaction extent can provide a potential on‐purpose ethylene technology. In the present paper, CeO2 is proposed to be a promising catalyst, while the deep oxidation process of dry reforming is preferred. The SiO2 coated CeO2 catalyst can render the reaction more selective towards ethylene. Through high sensitivity low energy ion scattering spectroscopy, findings were made that SiO2 only partially covered CeO2 in the Si0.1 CeO2 sample, in which the ethylene selectivity was 2.7 times as high as that of the bulk CeO2 based on the same conversion level. Further, density functional theory calculations also demonstrated that the presence of the SiO2 layer was more conducive to the desorption of ethylene. Abstract : Two‐in‐one : Oxidative dehydrogenation of ethane with CO2 combines the utilization of greenhouse gas and the valorization of light alkanes. CeO2 showed its potential in catalyzing the reaction, but the dry reforming was preferred. Partial coverage of CeO2 by porous SiO2 benefited to the desorption of intermediate ethylene, having the reaction be more selective towards the product of selective oxidation.